‘The family fight is on!’ - Anna-Maija Castrén (Nordisk Tidskrift för Socioonomastik)
Finnish marital surnaming practices give precedence to the husband’s surname as the family name after marriage. Legislation treats partners symmetrically and offers alternatives, but a patriarchal mindset still has a hold on the transition to a family. This article analyses interviews of 19 mixed-sex wedding couples and focuses on how they resort to humour in discussing alternatives to patrilineal practice. Literature shows that humour plays an important role in maintaining and regulating close relationships, but it can also be used as an indirect way to dismiss partners’ concerns. The results of this exploratory and descriptive analysis of couple interviews highlight different ways in which humour is used when discussing the potentially sensitive matter of marital surnaming.